Enhanced perfusion in eyes and cerebral perfusion defects in a patient with fragile X syndrome - Balci, Tansel Ansal; Ciftci, Ismail; Kabakus, Nimet; Aydin, Mustafa (Tohoku Univ Medical Press, 2006)
Fragile X syndrome (FXS) is known as the most common form of inherited mental retardation. In our study, brain perfusion single photon emission computed tomography (SPECT) was performed in a 6 year-old boy diagnosed with FXS. Diffuse bilateral uptake of Technetium-99m hexamethyl propylene amine oxime (99mTc-HMPAO) was noted in his orbits, as well as cortical perfusion defects (hypoperfusion in the right parietal and the left temporal lobe). Ophthalmologic examination showed no pathological findings. Magnetic resonance imaging (MRI) revealed no abnormality in the orbital structures, although hypoplasia of cerebellum and vermis was visualized. Since the patient was crying during the injection, the increased blood flow or the increased metabolism of the eyes and/or ocular muscles may be responsible for this orbital finding. Alternatively, the enhanced uptake of HMPAO in the, orbits may reflect the pathology associated with FXS, because patients with FXS might have visual-motor abnormalities. To the best of our knowledge, there has been no report documenting such an orbital uptake of HMPAO. Moreover, the visualization of decreased cerebral perfusion, with the normal findings of MRI, indicates that brain SPECT imaging with HMPAO is helpful for detecting brain abnormalities in children with FXS.
Keywords: Tc-99m HMPAO; brain scintigraphy; orbital uptake; cerebral perfusion; fragile X syndrome